Chickpea seed vigor evaluated by computerized seedling analysis - Araújo, Joyce de Oliveira; Dias, Denise Cunha Fernandes dos Santos; Medeiros, André Dantas de; Silva, Laércio Junio da; Nascimento, Warley Marcos (Semina: Ciências Agrárias, 2021)
Computerized seedling analysis is a promising tool for assessing seed vigor, providing reliable and less subjective results. The aim of this study was to define a method for evaluating the vigor of chickpea seeds through computerized image analysis, using the Seedling Analysis System (Sistema de Análise de Plântula - SAPLÂ®) as a basis. Two chickpea cultivars were evaluated, consisting of five seed lots of cv. BRS Aleppo and four seed lots of cv. Cícero. Test were performed on the seeds of each cultivar for initial characterization of the physiological potential of the lots, and the results were compared with the determinations made via SAPLÂ®. The results showed high correlations between the variables obtained from computerized analysis and from traditional vigor tests, especially for the close relationship between the cold test and low temperature germination test with the corrected vigor index (r > 0.9) evaluated on the fourth day after the beginning of the test. The total length of seedlings, length of the primary root, and growth and corrected vigor indices obtained through computerized analysis of seedlings on the 4th day after sowing allowed separation of the lots regarding vigor. Computerized analysis of seedlings using SAPLÂ® is effective in determining the vigor of chickpea seed lots.